DEVELOPMENT OF THE MODERN THEORY OF ANALYSIS AND ITS SPECIFICITY - PORTOVARAS, Tetiana (Scientific journal «World of Finance», 2024)
Introduction. The new challenges of the modern economy, which arose as a result of the martial law and must be taken into account in the process of conducting analysis at all levels of managerial activity of economic entities, encourage the use of new tools and methods of assessment and preparation of information for management and require a rethinking of scientific approaches to synergism and complexity of this process.The purpose of the article is to conduct in-depth studies of the theoretical foundations of economic analysis, to identify the key reasons for the emergence of its modern types, to highlight and critically evaluate its characteristics and directions for the formation of proposals regarding directions for the further development of this management function, taking into account current challenges and risks.Results. In the process of the conducted scientific research, the types of economic analysis were identified, which will allow to determine the direction of the research taking into account all the necessary components. It is proposed to carry out the distribution of economic analysis according to the scope of its application, which will allow to precisely determine which analysis should be carried out in accordance with the management tasks of the economic entity. The main prospective types of economic analysis that correspond to modern challenges and risks and determine the possibilities of development of subjects in a competitive market environment are substantiated. It is proposed to carry out regulatory and legal analysis and computer analysis in the course of the business entity's activity, which will allow to fully reflect the quality of work of all levels of management and make it possible to choose the most effective direction for the further development of the business entity in the long term.Prospects. The modern development of the economic system and the threats that arise in the process of managerial activity of business entities require analysts to quickly process economic data and derive their results in accordance with the specified terms. And therefore, the subject of further scientific research is the use of the capabilities of computer technologies in the process of conducting effective and qualitative analysis for the purposes of managing a business entity in order to solve problem situations.